2014
DOI: 10.1371/journal.pone.0102233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV Infection on the Metabolic and Hormonal Status of Children with Severe Acute Malnutrition

Abstract: BackgroundHIV infection occurs in 30% of children with severe acute malnutrition in sub-Saharan Africa. Effects of HIV on the pathophysiology and recovery from malnutrition are poorly understood.MethodsWe conducted a prospective cohort study of 75 severely malnourished Ugandan children. HIV status/CD4 counts were assessed at baseline; auxologic data and blood samples were obtained at admission and after 14 days of inpatient treatment. We utilized metabolomic profiling to characterize effects of HIV infection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Lipid alterations in HIV-infected individuals receiving protease inhibitors based antiretroviral treatment determined using untargeted metabolomic profiling of plasma, has been previously linked to markers of inflammation, microbial translocation, and hepatic function, suggesting that dysregulated innate immune activation and hepatic dysfunction are occurring among HIV antiretrovirally-treated individuals[11]. Furthermore, metabolomic profile in HIV-infected children shows hypoleptinemia and hypoadiponectinemia and is the activation of critical adipose tissue storage and function in the adaptation to malnutrition[30]. Also, alterations in the Cerebrospinal fluid metabolome among HIV antiretrovirally-treated individuals harboring HIV-associated neurocognitive disorders reveal that persistent inflammation, glial responses, glutamate neurotoxicity, and altered brain waste disposal are associated with cognitive alteration[31].…”
Section: Resultsmentioning
confidence: 99%
“…Lipid alterations in HIV-infected individuals receiving protease inhibitors based antiretroviral treatment determined using untargeted metabolomic profiling of plasma, has been previously linked to markers of inflammation, microbial translocation, and hepatic function, suggesting that dysregulated innate immune activation and hepatic dysfunction are occurring among HIV antiretrovirally-treated individuals[11]. Furthermore, metabolomic profile in HIV-infected children shows hypoleptinemia and hypoadiponectinemia and is the activation of critical adipose tissue storage and function in the adaptation to malnutrition[30]. Also, alterations in the Cerebrospinal fluid metabolome among HIV antiretrovirally-treated individuals harboring HIV-associated neurocognitive disorders reveal that persistent inflammation, glial responses, glutamate neurotoxicity, and altered brain waste disposal are associated with cognitive alteration[31].…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Inflammation of the small intestine in EED is associated with high C-reactive protein levels and may be accompanied by release of cytokines that reduce appetite and food intake 35 and impede production and action of chondrocyte growth factors. Recent studies 36,37 found that stunted, malnourished Ugandan infants and children (age 6 months-5 years) had high levels of interleukin 6 (IL-6), which blocks growth hormone induction of insulin-like growth factor 1 (IGF-1) production and inhibits IGF action at the growth plate. 38,39 Likewise, IL-6 levels were elevated soon after delivery in a subset of Zimbabwean infants with LBW.…”
Section: Growth Failure and Stunting In Malnutrition And Eedmentioning
confidence: 99%
“…Malnutrition is often the presenting clinical feature on initial human immunodeficiency virus (HIV) diagnosis in sub‐Saharan African children and is a significant risk factor for mortality . The causes of malnutrition in this setting are multifactorial including delays in HIV diagnosis and ART initiation with resultant increased energy expenditure and basal metabolic rate together with higher rates of opportunistic infections, diarrhoea, malabsorption, food insecurity and poverty …”
Section: Introductionmentioning
confidence: 99%
“…3 The causes of malnutrition in this setting are multifactorial including delays in HIV diagnosis and ART initiation with resultant increased energy expenditure and basal metabolic rate together with higher rates of opportunistic infections, diarrhoea, malabsorption, food insecurity and poverty. 4,5 Severely malnourished HIV-infected children experience impaired immunological and virological responses and higher mortality 6,7 compared to their nonmalnourished counterparts despite nutritional rehabilitation and ART. 8,9 Altered pharmacokinetics (PK) of antiretroviral medications in malnourished children may be an important contributor to these poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%